Functional customization: Value creation by individual storage elements in the car interior. - Wagner, A.-S.; Kilincsoy, Ü.; Reitmeir, M.; Vink, P. (Work, 2016)
BACKGROUND: Mobility demands change due to differing life stages of car owners. Car sharing and retail markets seldom offer a possibility for customization by the user in contrast to the freedom of choice of an initial owner of a car. OBJECTIVE: The value creation of functional customization is investigated. Prior to a test with a concept design, different use case scenarios of car drivers are identified regarding the preferred storage location of their personal belongings in different situations. METHODS: A study with 70 subjects was conducted in order to evaluate the value added by functional customization. Storage habits of users were investigated in general and in relation to a concept design offering the possibility for flexible storage. RESULTS: Smartphones, supplies, beverages and wallets were the most relevant belongings in all driving situations (commuting, leisure, vacation and special occasions) complemented by sports equipment. Smartphones and other valuables are stored within reach and sight of the user. The emotional responses, recorded before and after the test, subdivided in attraction, hope and joy indicated positive feedback. CONCLUSIONS: The ease of use and the design proved to be crucial product characteristics of individually adaptable storage solutions. Positive emotions are contributing factors for a user's purchasing decision.